Alat Pacu Jantung Tanpa Kabel - Albert Sudharsono; Dicky A. Hanafy; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2016)
The development of health technology benefits in the treatment of heart rhythm abnormalities. Cardiac pacemakers with nonsurgical methods plays a critical role in the management of patients with heart rhythms disorders. The discovery of a leadless pacemaker provides many benefits compared to conventional pacemaker where the device can be implanted by transcatheter delivery. Various studies have been done and still continued to monitor the efficacy and safety of this device. In principle, Indonesia is ready to participate in the advance technology of leadless pacemaker. National Health Covarage policy will play an important role in this new technology in the future.